The Representation of Āzar and Terah in the Qur'an and the Bible: Julia Kristeva's Intertextuality Perspective - Auzia, Nadia Tamara Rifa; Safitri, Nuraisyah (Direktorat Pondok Pesantren Universitas Islam Indonesia, 2025)
This paper examines the representation of the figure of Prophet Ibrahim's father in the Qur'an and the Bible through Julia Kristeva's intertextuality approach. The focus of the study is on the aspects of the characters' identities (Āzar and Terah), their positions of faith, and the narratives regarding the end of their lives. In the Bible, Terah is referred to as Abraham's father and depicted historically without explicit theological confrontation. Conversely, the Qur'an refers to Āzar as Ibrahim's father and positions him as a symbol of rejection of monotheism. A striking difference emerges in the narratives of their final days: the Bible implies a peaceful death for Terah, while the Qur’an explicitly states that Āzar died in polytheism. Through the principles of defamiliarization, expansion, and demystification in intertextuality theory, this study demonstrates that the Qur’an does not merely respond to previous narratives but redefines theological meaning to affirm a distinctive identity of faith. This study affirms that sacred texts do not stand alone but exist in a dialogical relationship that allows for shifts, reinterpretations, and the reshaping of meaning across traditions. [Tulisan ini mengkaji representasi sosok ayah Nabi Ibrahim dalam Al-Qur’an dan Alkitab melalui pendekatan intertekstualitas Julia Kristeva. Fokus kajian diarahkan pada aspek identitas tokoh (Āzar dan Terah), posisi keimanan mereka, serta narasi mengenai akhir kehidupan mereka. Dalam Alkitab, Terah disebut sebagai ayah Abraham dan digambarkan secara historis tanpa konfrontasi teologis yang eksplisit. Sebaliknya, Al-Qur’an menyebut Āzar sebagai ayah Ibrahim dan memposisikannya sebagai simbol penolakan terhadap tauhid. Perbedaan mencolok terlihat dalam narasi akhir kehidupan mereka: Alkitab mengisyaratkan kematian Terah yang damai, sedangkan Al-Qur’an secara tegas menyatakan bahwa Āzar wafat dalam kemusyrikan. Melalui prinsip-prinsip defamiliarisasi, ekspansi, dan demistifikasi dalam teori intertekstualitas, penelitian ini menunjukkan bahwa Al-Qur’an tidak sekadar merespons narasi sebelumnya, tetapi juga mendefinisikan ulang makna teologis untuk menegaskan identitas iman yang khas. Penelitian ini menegaskan bahwa teks-teks suci tidak berdiri sendiri, melainkan hadir dalam relasi dialogis yang memungkinkan terjadinya pergeseran, reinterpretasi, dan pembentukan ulang makna lintas tradisi.]